Membangun Kelompok Mahasiswa Peduli Lingkungan Melalui Penanaman Mangrove Pencegah Banjir Rob Jakarta - Deni Nasir Ahmad (Universitas Mataram, 2019)
The purpose of community service activities is to provide knowledge and direct experience to students about the effects of tidal floods and improve the environment affected by tidal flooding through mangrove or mangrove replanting activities on vacant land around the coast or coastline. The method used is field recovery and community service where the activity is divided into several activities, including: a. the introduction of mangroves and how they are planted and how they grow and develop. b. presentation of material about tides or tides in the Jakarta sea that entered the Jakarta coastline area, the impact and problems if open land around the coast is gone. c. open land planting activities around Pantai Indah Kapuk-Muara Angke, North Jakarta. The results of the activities are a. Presentation of Material Regarding Mangrove Plants and Jakarta Sea Tides. b. mangrove planting in open fields. Summary of activities are a. that mangrove land in the Jakarta area, especially in the Pantai Indah Kapuk-Muara Angke region, North Jakarta has experienced a narrowing which resulted in the area of catchment and retaining sea tides or Jakarta has experienced a slight function. b. With the existence of field recovery activities and community service, students are expected to get direct experience and be able to solve problems that occur in the surrounding environment. c. The function of mangrove land is very important for the preservation and diversity of swamps or mangrove land.Keywords: Mangrove Plants; Rob Jakarta; Environmental Concern.